Analisis Pengaruh Strategi Pemasaran dan Kualitas Layanan Dalam Upaya Menarik Minat Terhadap Produk-Produk dan Jasa Perbankan Konvensional dan Syariah Pada Masyarakat Provinsi Jambi - Ary Dean Amri; Anitha Octaviani; Rosnaida Rosnaida; Sekar Adinda Putri; Nurita Nurita; Noviva Rita; Syahrul Gunawan; Adinda Putri Agustina (Universitas Islam Negeri Sumatera Utara, 2023)
This study aims to analyzing how big the factors of marketing strategy and service quality are in an effort to attract interest in conventional and Syariah banking products and services for the people in Jambi Province. This research method uses quantitative research methods. The object of this research is the people that lived in Jambi Province, totaling 471 respondents. Based on the results of the T test and F test variable (X1) marketing strategy factor and variable (X2) service quality factor obtained a significant value of 0.000 <0.005. So it can be concluded that the variable (X1) the marketing strategy factor and variable (X2) the service quality factor are influential in efforts to attract interest in conventional (Y1) and Syariah (Y2) banking products and services of the people in Jambi Province. Based on the results of the coefficient of determination variable (X1) marketing strategy factors and variables (X2) service quality factors influence 60.0%: 63.6% and 64.3%: 67.5% in an effort to attract interest in products and services conventional banking (Y1) and Syariah (Y2). The results of the study also show that the people in Jambi Province are more dominantly interested in products and services of Islamic banking: conventional banking by 73.1%: 43.9%. Thus the results of the study indicate that the service quality factor is more dominant in an effort to attract interest in conventional and Syariah banking products and services in the people of Jambi Province.